"A New Philosophy for International Law" and Dworkin's Political Realism. Issue 1 (2nd February 2016) - Scarffe, Eric J.
Abstract : During his career, Ronald Dworkin wrote extensively on an impressive range of issues in moral, political, and legal philosophy, but, like many of his contemporaries, international law remained a topic of relative neglect. His most sustained work on international law is a posthumously published article, "A New Philosophy for International Law" (2013), which displays some familiar aspects of his views in general jurisprudence, in addition to some novel (though perhaps surprising) arguments as well. This paper argues that the moralized account of international law we might have expected is conspicuously missing from this posthumous article; with Dworkin advancing an argument based on a form of political realism instead.